2015
DOI: 10.5812/aapm.21061
|View full text |Cite
|
Sign up to set email alerts
|

A New Technique to Treat Facet Joint Pain With Pulsed Radiofrequency

Abstract: Introduction:Facet joint pain affects 5% to 15% of the population with low back pain and the prevalence increases with age due to progression of arthritis. While conservative treatments are often unsuccessful, the scientific evidence on minimally invasive therapies such as intra-articular steroid infiltration and continuous and pulsed radiofrequency (PRF) of the medial branches is contradictory. Since PRF has recently been reported to successfully treat joint pain, a new application of this method is proposed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…[28] Finally, the electrical field was reported to reduce the production of proinflammatory or inflammatory cytokines. [26] After the application of PRF into the joint, serum C-reactive protein and cytokines were reduced. [26] In our study, IA PRF stimulation of the LFJ seems to reduce the IA inflammation, leading to reduction of LFJ-origin pain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[28] Finally, the electrical field was reported to reduce the production of proinflammatory or inflammatory cytokines. [26] After the application of PRF into the joint, serum C-reactive protein and cytokines were reduced. [26] In our study, IA PRF stimulation of the LFJ seems to reduce the IA inflammation, leading to reduction of LFJ-origin pain.…”
Section: Discussionmentioning
confidence: 99%
“…[26] After the application of PRF into the joint, serum C-reactive protein and cytokines were reduced. [26] In our study, IA PRF stimulation of the LFJ seems to reduce the IA inflammation, leading to reduction of LFJ-origin pain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As for the other 6 previous studies, 2 prospective observational studies, 3 retrospective studies, and 1 case report were reported. In all 6 studies, after medial branch or IA PRF stimulation, significant pain reduction and functional improvement were observed.…”
Section: Resultsmentioning
confidence: 97%
“…Thus far, 10 previous studies have reported the effect of PRF stimulation on lumbosacral facet joint pain . Of these, 4 studies were randomized trials .…”
Section: Resultsmentioning
confidence: 99%